PENGARUH EXPERIENTIAL MARKETING TERHADAP KEPUASAN KONSUMEN DAN MINAT BELI ULANG DI WARUNG KOPI KLOTOK, KALIURANG, YOGYAKARTA - Febrini, Irma Yanti; PA, Retno Widowati; Anwar, Misbahul (Jurnal Manajemen Bisnis, 2019)
This research is about analyzing the influence of Experiential Marketing on consumer satisfaction and repurchase intention at Warung Kopi Klotok, Kaliurang, Yogyakarta. It is a marketing element for the repurchase intention who obtain customer satisfaction through elements of experiential marketing, namely sense, feel, think, act, and relate. Obtaining data directly through a distribution questionnaire, with the number of samples meeting the requirements of a purposive sample of 247 respondents. The data analysis technique used in this study is Structural Equation Modelling (SEM) with the Moment Structure Analysis (AMOS) program version 22. The results of the study show four conclusions namely experiential marketing has a positive and significant effect on customer satisfaction, experiential marketing has a positive and significant effect on repurchase intention, customer satisfaction has a positive and significant effect on repurchase intention, and customer satisfaction is able to mediate marketing experience to repurchase intention.